2022
DOI: 10.1016/j.psj.2021.101520
|View full text |Cite
|
Sign up to set email alerts
|

Research Note: Effects of cage and floor rearing systems on growth performance, carcass traits, and meat quality in small-sized meat ducks

Abstract: This study was performed to evaluate the effects of different rearing methods on the growth performance, carcass yield, and meat quality of small-sized meat ducks. A total of 420 healthy 21-day-old birds was randomly allocated to 2 treatment groups (6 replicates per treatment, sex ratio 1/1) and subjected to 2 rearing methods (furnished cage and plastic wire-floor) until d 63. Growth performance was measured in all birds. Three males and 3 females from each replicate were randomly selected and evaluated to det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
18
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 25 publications
4
18
2
Order By: Relevance
“…Slaughter performance is considered as an important measure of the economic profit of meat farm animals. In this study, the yields of the defeathered, semieviscerated, and eviscerated carcass were above 81%, 76%, and 69%, respectively, which is in accordance with the results of our previous study ( Bai et al, 2022 ). Interestingly, low RFI did not significantly affect the slaughter performance, including the yields of the defeathered, semieviscerated, eviscerated carcass, breast muscle, thigh muscle, lean meat, gizzard, and abdominal fat ( P > 0.05).…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Slaughter performance is considered as an important measure of the economic profit of meat farm animals. In this study, the yields of the defeathered, semieviscerated, and eviscerated carcass were above 81%, 76%, and 69%, respectively, which is in accordance with the results of our previous study ( Bai et al, 2022 ). Interestingly, low RFI did not significantly affect the slaughter performance, including the yields of the defeathered, semieviscerated, eviscerated carcass, breast muscle, thigh muscle, lean meat, gizzard, and abdominal fat ( P > 0.05).…”
Section: Resultssupporting
confidence: 93%
“…In this study, the results demonstrated that the WLR of ducks was slightly higher in the LRFI group, suggesting lower water-holding capacity. Generally, a higher L* value, lower a* value, and higher drip loss represent poor meat quality ( Bai et al, 2022 ). Fortunately, there were almost no differences in the traits of breast and thigh muscles between the HRFI and LRFI small-sized meat ducks ( P > 0.05), which is in accordance with the results of high-, medium-, and low-RFI chickens ( Yang et al, 2020 ), and efficient- and inefficient-RFI cattle ( Nascimento et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Artificial insemination ( AI ) technology of poultry began in the 1930s, while AI for duck due to its low fertilization rate, its development and application is far lower than chicken. In recent years, with the transformation of duck raising system from traditional floor rearing to cage rearing ( Bai et al, 2022 , Zhang et al, 2019 ), the original natural mating mode will be gradually replaced by AI ( Qingyuan et al, 2021 ). In the process of AI, the semen quality of drakes plays a major role ( Ukaszewicz et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…To improve the production efficiency of duck eggs, rearing of laying ducks has gradually changed from traditional free-rearing to cage rearing to achieve large-scale intensive production. Most previous studies have focused on the effects of different rearing systems on the feed conversion rate and production performance of laying ducks ( Zhang et al, 2018 ; Bai et al, 2022 ). However, few studies have explored the effects of different rearing systems on the differences in egg flavor and gut microbiota of laying ducks.…”
Section: Introductionmentioning
confidence: 99%